Acute myeloid leukemia presenting in oral cavity - A report of two cases - A Winnifred Christy; T Jones Raja Devathambi; B Deepika Lakshmi; Gheerthana Venkatesh (Wolters Kluwer Medknow Publications, 2021)
Acute myeloid leukemia is a malignant disease of the bone marrow. Because of its high morbidity, early diagnosis and prompt treatment are essential to save lives. This article describes the case reports of a 33-year-old female and a 60-year-old male who came to our dental hospital with gingival overgrowth, gingival bleeding, epistaxis, and facial swelling for about 1 week. After doing a thorough hematological examination, acute myeloid leukemia was diagnosed The oral health care professionals need to be able to recognize oral physiological characteristics, and, when identifying a change of normalcy, investigate it requesting additional tests or referring the patient to a specialized professional.